An historical grammar of Japanese - Sansom, George (The Clarendon press, 1928)
In the following study of the development of the Japanese language, it has been necessary for reasons of space as well as simplicity to concentrate on a description of the earliest and the lastest forms, those of the Nara and hein periods and of the present day, without paying much attention to the intervening stages.